Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Bioaugmentation for bioremediation: the challenge of strain selection - Ian P. Thompson; Christopher J. Van Der Gast; Lena Ciric; Andrew C. Singer (Environmental Microbiology, 2005)
Summary Despite its long‐term use in bioremediation, bioaugmentation of contaminated sites with microbial cells continues to be a source of controversy within environmental microbiology. This largely results from its notoriously unreliable performance record. In this article, we argue that the unpredictable nature of the approach comes from the initial strain selection step. Up until now, this has been dictated by the search for catabolically competent microorganisms, with little or no consideration given to other essential features that are required to be functionally active and persistent in target habitats. We describe how technical advances in molecular biology and analytical chemistry, now enable assessments of the functional diversity and spatial distribution of microbial communities to be made in situ . These advances now enable microbial populations, targeted for exploitation, to be differentiated to the cell level, an advance that is bound to improve microbial selection and exploitation. We argue that this information‐based approach is already proving to be more effective than the traditional ‘black‐box’ approach of strain selection. The future perspectives and opportunities for improving selection of effective microbial strains for bioaugmentation are also discussed.

The chemical cell biology of zinc: structure and intracellular fluorescence of a zinc-quinolinesulfonamide complex - M. Sarwar Nasir; Christoph J. Fahrni; David A. Suhy; Kevin J. Kolodsick; Christopher P. Singer; T. V. O'Halloran (JBIC Journal of Biological Inorganic Chemistry, 1999)